HISTÓRIA, FOTOGRAFIAS E PAISAGEM: O IMPACTO DA CHEGADA DO “MODERNO” EM COMUNIDADES FAXINALENSES DE REBOUÇAS –PR (1960 – 2017) - Langaro , Sonia Vanessa (2017)
The present research seeks to identify elements that presented changes over time in the landscapes and daily practices corresponding to the traditional communities known as faxinal, using photographs of the past and the present as the main source. The temporal delimitation is taken from the second half of the XX century until the present year of 2017. The spatial cut considered, refers to the three rural communities located in the municipality of Rebouças-PR, these being: Faxinal do Salto and Faxinal do Barreirinho Beltrão, which are considered active faxinal, and Faxinal de Francos, which is in the condition of inactive faxinal. The faxinais correspond to a traditional and community organization, having as main attributes the presence of native forests, farmland and a common breeding ground, constituting itself as a form of organization peculiar to the rural environment of Paraná. It occurs that large-scale commercial agriculture coupled with intense agricultural mechanization has increasingly advanced the faxinal areas, contributing to its disruption. In this way, the active faxinais undergo losses in their territorial area with consequent changes in vegetation, planting lands and internal community relations, being necessary a reorganization among the members of these communities so that they can keep alive the faxinalenses practices before certain pressures. As for unstructured faxinals, there remain only the memories of the traditional way of life disaggregated by its antagonists (mainly by the commercial agriculture allied to the lack of support of the public power) that have their vestiges recorded in photographs and narratives. Among the methodological procedures and sources used to carry out this research, we highlight the interpretation of old and recent photographs, bibliographical review, field trips and information provided by community dwellers, as well as oral history. The use of photographs as a source has an emphasis on this research, as they are presented as a vast documentary source for the discussion of issues related to the changes occurring in faxinal communities, especially those corresponding to the landscapes of these communities. In this research, the landscape is interpreted from the historical perspective, being taken as an element transformed by the action of man over time, that is, the landscape is discussed within the scope of temporality. At the end of this analysis, it was possible to observe how agricultural mechanization and the increasing commercial advance of soybean, corn, potato, tobacco, eucalyptus and pine trees altered the landscapes in the faxinais in question, as well as their traditional way of life, To a reflection on his faxinalense identity in the face of the pressures occasioned by his antagonists. In this sense, it was possible to draw a panorama of the transformations occurred in the faxinais surveyed; Present some weights of subjects involved in this process, and outline the importance of developing effective public policies for this scenario.